2011
DOI: 10.1002/cncr.26254
|View full text |Cite
|
Sign up to set email alerts
|

Serum cell‐free DNA in renal cell carcinoma

Abstract: BACKGROUND: Currently, there are no established diagnostic and prognostic serum markers for renal cell carcinoma (RCC). The objective of this study was to evaluate the putative significance of serum cell-free DNA. METHODS: Preoperative serum samples from 200 consecutive patients with sporadic, solid renal tumors were analyzed (157 patients with RCC and 43 patients with benign renal tumors). Quantitative real-time polymerase chain reaction was used to assess total cell-free DNA (ring finger protein 185 [RNF185]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 31 publications
5
52
0
Order By: Relevance
“…Circulating cfDNA, a biomarker that is easily accessible and preferably noninvasive, has been shown to have diagnostic and prognostic potential in RCC [12,19]. As necrosis is the predominant type of cell death in tumor tissue, longer DNA fragments representing non-apoptotic DNA may be a suitable marker in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cfDNA, a biomarker that is easily accessible and preferably noninvasive, has been shown to have diagnostic and prognostic potential in RCC [12,19]. As necrosis is the predominant type of cell death in tumor tissue, longer DNA fragments representing non-apoptotic DNA may be a suitable marker in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First, CFD elevation is not specific for RCC. Elevated CFD levels have been observed in patients with different types of malignancies [6][7][8] as well as nonmalignant etiologies, such as trauma, systemic inflammatory disorders, pulmonary embolism, and acute myocardial infarction [11]. Second, the present study cohort is small and heterogeneous (mixed first and advanced treatment lines) and, thus, in a larger and homogeneous cohort, other factors might have been associated with treatment outcome.…”
Section: Discussionmentioning
confidence: 85%
“…The results indicated that Wnt antagonist family genes detection had sensitivity of 79.0% and specificity of 75.8% and the serum DNA was significantly correlated with tumor grade and stage [36]. Besides, other studies have reported that some genes are highly specific for RCC patients in the level of DNA hypermethylation including VHL (91%) and RASSF1A (93%) [37]. Recently, another similar outcome showed that two genes, SMPD3 and FBXW10, are hypermethylated in ccRCC tissue samples compared with paired normal tissues.…”
Section: Epigenetic Biomarkers In Kidney Cancermentioning
confidence: 99%